A poly (octanediol citrate)/gallium-containing bioglass composite for bone tissue regeneration / Ehsan Zeimaran - Ehsan , Zeimaran (2016)
Bone can be affected by osteosarcomae requiring surgical excision of the tumor as part of a treatment regime. Complete removal of cancerous cells is difficult and conventionally requires the removal of a margin of safety around the tumor to offer improved patient prognosis. Gallium has been shown to be clinically effective, both against bone resorption and for the treatment of cancer-related hypercalcemia. This work considers a novel series of composite scaffolds based on poly (octanediol citrate) (POC) impregnated with a gallium-containing bioactive glass (0.48SiO2-0.12CaO- 0.32ZnO-0.08Ga2O3, molar fraction) microparticles for possible incorporation into bone following tumor removal. The objective of this research was to fabricate and characterize these scaffolds and subsequently report on their mechanical, thermal, structural and biological properties. The porous microcomposite scaffolds, with various concentrations of bioactive glass (10, 20, 30 wt%) incorporated, were fabricated using a salt leaching technique. The scaffolds exhibited compression moduli in the range of 0.3-7 MPa. The addition of bioactive glass increased the mechanical properties even though porosity increased. Furthermore, increasing the concentration of bioactive glass had a significant influence on glass transition temperature from 2.5 °C for the pure polymer to approximately 25 °C for 30 % bioactive glass-containing composite. The ion release study revealed that composites containing 30 % bioactive glass had the highest ion release ratio after 28 days of soaking in phosphate buffered saline (PBS). The interaction of the bioactive glass phase with POC led to the formation of additional ionic crosslinks, aside from the covalent crosslinks, which further resulted in increased stiffness and decreased weight loss. The antibacterial activity of these scaffolds was investigated against both Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli) bacteria in vitro. The ability of the scaffolds to release ions and the subsequent ingress of these ions into hard tissue was evaluated using a bovine bone model. Scaffolds containing bioactive glass exhibited antibacterial activity which increased with higher bioactive glass loads; viable cells decreased to about 20 % for the composite scaffold containing 30 % bioactive glass. The Ga3+ release rate increased as a function of time and Zn2+ was shown to incorporate into the surrounding bone. The effect of composite scaffolds on growth and osteogenic differentiation of human osteoblast-like cells and human bone marrow-derived mesenchymal stem cells (hBMSCs) was investigated. The osteoblastlike cells were well attached and growth on composites and collagen synthesis increased particularly with the 10 % bioactive glass concentration. All the scaffolds were able to support the growth of hBMSCs and guide their osteogenic differentiation without osteogenic media stimulation. The expression of bone-associated genes (collagen I, osteonectin and osteocalcin, bone morphogenetic protein 2, runt-related transcription factor 2) was significantly increased by a culture time for of up to 2 weeks, particularly for the composite scaffolds loaded with 10 % bioactive glass. The composite scaffolds significantly stimulated alkaline phosphatase (ALP) activity compared to the pure POC scaffolds. Cellular mineralization of the secreted extracellular matrix illustrated a higher calcium level on the composites than pure POC, and increased with culture time. These results suggest that composite scaffolds of POC and a bioactive glass doped with therapeutic elements provides favourable conditions for osteogenic differentiation of hBMSCs and can potentially be used to induce bone healing and regeneration.